1979
DOI: 10.1128/aac.15.3.368
|View full text |Cite
|
Sign up to set email alerts
|

Avermectins, New Family of Potent Anthelmintic Agents: Isolation and Chromatographic Properties

Abstract: The avermectins, a family of new anthelmintic agents, were isolated from the mycelia of Streptomyces avermitilis. Four closely related major components and four homologous minor components were separated from the complex. Solvent extraction, solvent partition, and adsorption methods were used to isolate and purify the complex; novel partition chromatography systems using Sephadex LH-20 were used to separate the components. A reverse-phase high-pressure liquid chromatography assay for the quantitative determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(80 citation statements)
references
References 2 publications
0
79
0
1
Order By: Relevance
“…The anthelmintic activity of the avermectins was first detected in 1979 (Miller et al, 1979). Ivermectin is a pioneering drug, a dihydro derivative of avermectin, originating from a microorganism isolated at Tokyo, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…The anthelmintic activity of the avermectins was first detected in 1979 (Miller et al, 1979). Ivermectin is a pioneering drug, a dihydro derivative of avermectin, originating from a microorganism isolated at Tokyo, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Ivermectin is a group of macrocyclical lactones, derived from 22,23-dihydro avermectin B1, with low water solubility that is produced by Streptomyces avermectilis (Burg, et al, 1979;Egerton et al, 1979;Miller et al, 1979;Chabala et al, 1980), being largely used as anti-parasitic in the domestic animals (Aziz et al, 1982;Campbell et al, 1983). Previous studies have shown that the avermectins are lethal for immature and adult stages of some insect orders (Strong and Brown, 1987) and efficient for the control of Culex quinquefasciatus (Freitas et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The avermectin family displayed extraordinarily potent anthelmintic properties. [15][16][17] Ivermectin is a safer, more potent semisynthetic mixture of two chemically modified avermectins, comprising 80% of 22,23-dihydroavermectinB1a and 20% 22,23-dihydroavermectin-B1b (Figure 3). …”
Section: The Past: Unmatched Successesmentioning
confidence: 99%